Separácia distálnej epifýzy humeru u 4-mesačného dojčaťa - Sýkora, L; Trnka, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2012)
We report the case of a 4-month-old infant with fracture-separation of the distal humeral epiphysis diagnosed on the basis of X-ray examination. Closed reduction was performed under ultrasound guidance. The effect of reduction was checked by computer tomography and magnetic resonance imaging and, under general anaesthesia, the arm was immobilised using a collar-and-cuff. Subsequently, percutaneous osteosynthesis with two 1.2-mm Kirschner wires through the radial condyle was carried out. The fracture was allowed to heal in a normal elbow position with plaster cast for 5 weeks. The duration of immobilisation had to be prolonged and removal of the wires postponed because the infant acquired a respiratory infection; the usual time for fracture union is 3 weeks. At 23 months after injury the outcome was excellent and the baby remained registered for a long-term follow-up.
Keywords: ženské pohlaví; Epiphyses; Female; Joint Dislocations; dislokace kloubu; Infant; kojenec; Humans; lidé; fraktury humeru; Radiography; Humeral Fractures; epifýzy; radiografie